Bovine viral diarrhea virus 2 strains generate deletion viral genomes primarily in the NS2 region of the viral genome - Holthausen, David J.; Bayles, Darrell O.; Neill, John D.; Dassanayake, Rohana P.; Falkenberg, Shollie M.; Nielsen, Daniel W.; Goldkamp, Anna K.; Menghwar, Harish; Casas, Eduardo (Frontiers in Veterinary Science, 2025)
Bovine viral diarrhea virus (BVDV) is a significant economic concern for the global cattle industry. This is attributed to the increased risk of transplacental BVDV infection during pregnancy, before sufficient maturation of the fetal immune system. This results in significant reproductive losses via spontaneous abortion as well as the birth of offspring that are persistently infected and immunotolerant to the non-cytopathic BVDV strain. These persistently infected cattle act as reservoirs and are the major source of BVDV transmission within the herd. Previously, we reported bioinformatic analyses showing that BVDV1a and 1b genotypes generate distinct sets of diverse deletion viral genomes (DelVGs) during the natural viral life cycle. DelVGs are generated by skipping events that occur during genome synthesis by the error-prone viral replication machinery. These replication-deficient genomes play many roles in host–pathogen interactions, contributing to the establishment of viral persistence. A total of 21 field isolates of the BVDV2 genotype were analyzed for the presence and characterization of DelVGs using Illumina MiSeq BVDV2 genome sequencing reads. BVDV2 strains generate significantly more Nonstructural protein 2 (NS2) DelVGs than any other region of the genome, with over 90% of those deletions having both 5` and 3` junctions within the NS2 region. BVDV2c strains produce approximately 150 times as many DelVG reads as BVDV2a strains. Of the BVDV2a isolates queried, cytopathic BVDV2a strains generated two times as many NS2 DelVG reads as compared to non-cytopathic BVDV2a strains.